Impact of alcohol-induced intestinal microbiota dysbiosis in a rodent model of Alzheimer’s disease - Frausto, Dulce M.; Engen, Phillip A.; Naqib, Ankur; Jackson, Aeja; Tran, Laura; Green, Stefan J.; Shaikh, Maliha; Forsyth, Christopher B.; Keshavarzian, Ali; Voigt, Robin M. (Frontiers in Aging, 2022)
Introduction: Alzheimer’s disease (AD) is a devastating neurodegenerative disorder. While genetics are important in the development of AD, environment and lifestyle contribute significantly to the development and progression of AD. One such lifestyle factor is alcohol consumption. Unhealthy and excessive chronic alcohol consumption is associated with a greater risk of all types of dementia, especially AD. Alcohol misuse disorder has numerous effects on the body including alterations to the intestinal microbiota (dysbiosis) and intestinal barrier dysfunction (leakiness, intestinal hyperpermeability), with compelling evidence indicating that the intestinal-derived inflammation as a consequence of dysbiotic microbiota and/or intestinal barrier dysfunction can promote neuroinflammation leading to detrimental impact on brain structure and function. Objective: We sought to determine the impact of alcohol-induced microbiota and intestinal barrier dysfunction on AD-like behavior and brain pathology using a transgenic rodent model of AD (3xTg-AD). Methods: Alcohol (EtOH, 20%) was administered to 3xTg-AD mice in the drinking water for 20 weeks. Intestinal (stool) microbiota, intestinal permeability, AD-pathology (phosphorylated tau, beta amyloid), microglial activation and phenotype and AD-relevant behavior were examined. Results: Administration of EtOH resulted in changes to the intestinal microbiota community (dysbiosis) and increased intestinal barrier permeability in both control and 3xTg-AD mice (oral/urine sugar test and lipopolysaccharide binding protein (LBP)). However, 20% EtOH did not increase the presence of beta amyloid or phosphorylated tau, promote microglial activation in the brain, or AD-related behavior in 3xTg-AD mice. Conclusion: Alcohol-induced microbiota dysbiosis and intestinal barrier dysfunction were not sufficient to exacerbate AD-like brain pathology or behavior in the 3xTg-AD mouse model of AD.